Investigation of cellulose separator in aluminium-air battery - Lye, Jun Yan (2024)
In the face of escalating energy demands and the imperative shift towards sustainable energy sources, batteries play a pivotal role in enabling this transition. Among the array of battery technologies, aluminum-air batteries stand out for their high energy density, cost-effectiveness, and abundance of aluminum resources. This study investigates the feasibility of utilizing cellulose-based separators which is fabricated by conifer cellulose in aluminumair coin cell batteries, addressing key challenges such as separator degradation and electrolyte byproduct formation. Through meticulous experimentation, various cellulose separators with different binders , weight ratios and total mass were evaluated for their performance. Results revealed significant variations in discharge behavior and peak power output based on binder type, weight ratio, and total mass by using both discharge and linear sweep voltammetry (LSV) test . Separator with carboxymethyl cellulose (CMC) binders produced shorter discharge periods and lower plateau voltages than polyvinyl alcohol (PVA)binders. Doubling overall mass while retaining the same weight ratio significantly enhanced performance, especially with carboxymethyl cellulose (CMC) binders, resulting in longer discharge times and higher peak outputs. The best-performing separator had 75% nanofibrils cellulose (CNF) and 25% carboxymethyl cellulose (CMC) by weight, for a total mass of 0.6g. This separator discharged in 1121 seconds with a discharge current of 20mA and a plateau voltage of 1.15V during the discharge test. In the LSV test, it achieved a peak power of 47.8mW. Therefore, the CNF75CMC25 separator weighing 0.6g was then used in an aluminum coin cell battery, resulting in a discharge time of 160 seconds, a plateau voltage of 1.15V, and a peak power of 12.4mW.